A Case of Lung Squamous Cell Carcinoma With Duodenal Metastasis on FDG PET/CT. (August 2016) - Cheng, Gang
Abstract : Abstract: Non–small cell lung cancer (NSCLC) tends to have distant metastasis. However, metastasis from NSCLC to the small bowel is uncommon, and duodenal metastasis from NSCLC is extremely rare. FDG PET/CT findings of duodenal metastasis from NSCLC have not been reported in the literature. In this case, we report FDG PET/CT findings in a 61-year-old NSCLC patient with biopsy-proven metastasis in the transverse duodenum.